Epidemiological Profile and Projections of Incidence and Mortality of Ischemic Heart Disease in Nepal: An Analysis of the Global Burden of Disease Study 2021 - He, Yao; Prajapati, Dipanker; Zhang, Yangjie; Gao, Keqin; Wang, Bole; Wang, Zifu; Liu, Yongbin (Nepalese Heart Journal, 2025)
Background and Aim: Ischemic heart disease (IHD) is a leading global cause of disability and mortality, yet systematic epidemiological analyses in Nepal remain scarce. This study aimed to analyze trends in IHD incidence and mortality in Nepal and project future burdens to inform evidence-based interventions. Methods: Data from the Global Burden of Disease Study 2021 were analyzed. Joinpoint regression identified trends in age- standardized incidence (ASIR) and mortality rates (ASMR), calculating the annual percent change (APC) and the average annual percent change (AAPC). Age-period-cohort (APC) models disentangled age, period, and cohort effects, while Bayesian APC models projected trends from 2022 to 2036. Risk factors were assessed via attributable mortality analysis. Results: From 1990 to 2021, Nepal experienced an increase in IHD incident cases from 49,265 to 116,482, with males consistently having higher ASIR than females. Recent trends (2015-2021) showed rising ASIR in both males and females, contrasting with global declines. ASMR declined in females (AAPC=-0.74%) but increased in males (AAPC=0.32%). Age effects revealed a steep increase in risk from 40-44 years, peaking at 7420.64/100,000 in the 95+ age group. Notably, post- 2007 birth cohorts showed a resurgent IHD incidence risk, representing an emerging threat to younger populations. Projections forecast ASIR rising to 466/100,000 (females) and 726/100,000 (males) by 2036, with male ASMR projected to increase to 260/100,000. For males, high systolic blood pressure; for females, solid fuel pollution were primary sex-specific IHD risk factors. Conclusion: Nepal’s IHD burden exhibits gender and age disparities, including a paradoxical rise in male mortality and resurgent risks in younger populations. Stratified intervention strategies are required, targeting gender-specific risks (hypertension management and tobacco control for males; clean fuel promotion and smoke-control cooking appliances for females) and age-specific needs (geriatric monitoring and intervention in primary healthcare and early health education for youth), alongside modifiable risk factors.